X-Ray Diffraction Studies of Mn(II) and Ni(II) Complexes of Benzoyl Acetone-L-Histidine - MUMTHAZ*, A.K.; PARAMESWARAN, GEETHA (Asian Journal of Chemistry, 2009)
Benzoyl acetone-L-histidine was synthesized by refluxing benzoyl acetone with L-histidine. This benzoyl acetone L-histidine (BAH) was used to synthesize Mn(II) and Ni(II) complexes having metal to ligand stiochiometry 1:1. The ligand and metal complexes were characterized by elemental analysis, molar conductivity, electronic absorption and IR absorption spectra. The magnetic nature of the complexes was established using Gouy's balance method. The XRD data was used to index the compound for orthorhombic system.